THE APPLICATION OF THE MIND MAPPING METHOD IN IMPROVING STUDENT LEARNING ACHIEVEMENT IN MADRASAH DINIYAH - Imamuddin Imamuddin; Walib Abdullah; Fatihul Iqbal Maulana Muhyin (LP2M Institut Agama Islam Al-Khiarat Pamekasan, 2023)
This research explores the effectiveness of the mind mapping method in improving students' learning outcomes at Madrasah Diniyah LPI MAKTUBA Palduding Plak-Pak Pegantenan Pamekasan. Using a qualitative descriptive approach, this study collected primary and secondary data to obtain an accurate and systematic description of the phenomenon under study. The results showed that the mind mapping method effectively improves student learning outcomes and can be applied in various learning contexts. However, this study has limitations, including focusing on one educational institution and using qualitative methods. For further research, exploring how the Mind Mapping method can be applied in teaching specific subjects or customised for students with special needs is recommended. This research makes an essential contribution to the field of education by demonstrating the potential of the mind-mapping method as a practical learning tool.